Cambodia : Ex Post Assessment of Longer-Term Program Engagement. (IMF Staff Country Reports; Country Report ;, 2004)
This Ex Post Assessment of Longer-Term Program Engagement for Cambodia reports its progress in implementing its economic stabilization, reconstruction, and reform programs. Prior to the normalization of relations with the IMF, Cambodia faced waves of rapid inflation and exchange rate depreciation, reflecting the government's recurrent resort to money creation to finance the fiscal deficit as external assistance withered. With monetary instability and negative real interest rates, financial intermediation levels and confidence remain low.